2008
DOI: 10.1210/me.2007-0455
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Element that Binds Basic Helix Loop Helix and Basic Leucine Zipper Transcription Factors Is Important for Gonadotropin-Releasing Hormone Regulation of the Follicle-Stimulating Hormone β Gene

Abstract: Although FSH plays an essential role in controlling gametogenesis, the biology of FSHbeta transcription remains poorly understood, but is known to involve the complex interplay of multiple endocrine factors including GnRH. We have identified a GnRH-responsive element within the rat FSHbeta promoter containing an E-box and partial cAMP response element site that are bound by the basic helix loop helix transcription factor family members, upstream stimulating factor (USF)-1/USF-2, and the basic leucine zipper me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 59 publications
3
41
1
Order By: Relevance
“…The finding that G␣ s contributed to suppression of FSH␤ mRNA was unexpected, as the FSH␤ promoter has been reported to have activating CREB sites that could be stimulated by G␣ s signaling (40). Experiments using separate individual G␣ s siRNAs and stimulatory experiments in the gonadotrope cell line and in primary mouse gonadotrope cells using CTX confirmed that the major effect of G␣ s signaling on FSH␤ expression was inhibitory.…”
Section: Discussionmentioning
confidence: 97%
“…The finding that G␣ s contributed to suppression of FSH␤ mRNA was unexpected, as the FSH␤ promoter has been reported to have activating CREB sites that could be stimulated by G␣ s signaling (40). Experiments using separate individual G␣ s siRNAs and stimulatory experiments in the gonadotrope cell line and in primary mouse gonadotrope cells using CTX confirmed that the major effect of G␣ s signaling on FSH␤ expression was inhibitory.…”
Section: Discussionmentioning
confidence: 97%
“…There is also a connection between G s and G q/11 signaling and Fsh␤ expression. CREB serves to integrate signals for basal-and GnRH-stimulated transcription of the rat FSH␤ gene (37), and the GnRH-responsive element contains a partial CRE site that binds CREB. Others have shown that GnRH induces binding of the AP-1 complex to the Fsh␤ promoter, and mutation of the AP-1 site reduces GnRH induction (33).…”
Section: Discussionmentioning
confidence: 99%
“…Introduced mutation of the E-BOX sequence was based on a previous work of Ciccone et al (35). For mutagenesis, the following primer pairs were used: 59-TCCACAGGGTGTACGGTAGCACATGCCACCACC-39 (m4f) and 59-GGTGGTGGCATGTGCTACCGTACACCCTGTGGA-39 (m4r); 59-GTCCCTGAAGTACCCTAGCAAAGAGGGTCAGGC-39 (m3f) and 59-GCCTGACCCTCTTTGCTAGGGTACTTCAGGGAC-39 (m3r); 59-CCC-AGATTGGCACCGTAGGGCGCCTGTCATCCT-39 (m2f) and 59-AGGA-TGACAGGCGCCCTACGGTGCCAATCTGGG-39 (m2r); and 59-GGTG-GGGGGTTGTACCTTAGCCACCTGTGTGGT-39 (m1f) and 59-ACCAC-ACAGGTGGCTAAGGTACAACCCCCCACC-39 (m1r).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%